Entomologische Chronik (James Edward Collin F. R. E. S., Ralph Leonard Coe). - Anonym (Beiträge zur Entomologie = Contributions to Entomology, 1969)
In memoriam James Edward Collin F. R. E. S. und Ralph Leonard Coe.